Autocrine activation of canonical BMP signaling regulates PD‐L1 and PD‐L2 expression in human dendritic cells. Issue 4 (16th February 2014) - Martínez, Víctor G.; Hidalgo, Laura; Valencia, Jaris; Hernández‐López, Carmen; Entrena, Ana; del, Beatriz G.; Zapata, Agustín G.; Vicente, Angeles; Sacedón, Rosa; Varas, Alberto
<x xml:space="preserve">Abstract</x> Bone morphogenetic proteins (BMPs) are multifunctional growth factors regulating differentiation and proliferation in numerous systems including the immune system. Previously, we described that the BMP signaling pathway is functional in human monocyte‐derived dendritic cells (MoDCs), which were found to express both the specific receptors and the Smad proteins required for signal transduction. In this study, we provide evidence that human MoDCs produce BMP‐4 and that this production is increased over the maturation process as is BMP signal transduction. When DCs are matured in the presence of an inhibitor of the BMP pathway, the expression of the maturation markers PD‐L1 and PD‐L2 is reduced, while cytokine production is not affected. As a result, these mature DCs present an augmented ability to stimulate both T cells and NK cells. Eventually, the inhibition of BMP signaling during maturation causes a reduced expression of IRF‐1, a transcription factor that positively regulates the expression of PD‐L1 and PD‐L2. The present study indicates that the BMP signaling pathway regulates PD‐L1 and PD‐L2 expression in human MoDCs during the maturation process, probably through the IRF‐1 transcription factor, and also points out that the manipulation of BMP signaling might considerably improve the immunogenicity of MoDCs used in immunotherapy.